The effects of dietary inclusion of Camelina sativa on performance and ascites incidence in broilers subjected to cold exposure - Farzaneh Hajiazizi; Amirali Sadeghi; Ahmad Karimi (Veterinary Medicine and Science, 2023)
Abstract Background Camelina sativa oilseed has a high amount of polyunsaturated fatty acids (FAs) especially α‐linolenic acid. n − 3 FA can improve the deformability of erythrocytes and mediate relaxations in coronary artery such as nitric oxide (NO) that is the principal vasodilator responsible for diminution the pulmonary arterial hypertension response. Methods To investigate the effects of camelina sources on ascites incidence in broilers kept on altitude, 672 male chicks were fed with 7 dietary treatments, including control, 2% or 4% camelina oil (CO), 5% or 10% camelina meal (CM) and 5% or 10% camelina seeds (CS) diets. Results Supplementation of 2% CO had no negative impact on performance, whereas feed intake and body weight gains decreased (p < 0.05) by adding 4% CO, CM and CS. Birds fed camelina diets had lower serum triglyceride at day 42, total cholesterol and LDL cholesterol at both 28 and 42 days. Plasma aspartate aminotransferase decreased (p < 0.001) among 5% and 10% CS groups on day 42. Serum and liver concentrations of malondialdehyde declined (p < 0.05) by camelina treatments, whereas serum NO and liver glutathione peroxidase activity significantly elevated. Red blood cell, heterophils and H:L ratio were lower but lymphocyte was higher in camelina groups. Inclusion of camelina reduced (p < 0.05) relative weights of heart and right ventricle, the weight of right ventricle to total ventricle ratio and ascites mortality. Conclusions Use of 2% CO as a source of n − 3 FA can improve ascites condition and mortality in broilers reared at high altitude without the reduction of growth performance. However, feeding 4% CO or 5% and 10% CS or CM reduced broiler performance.